TUGAS DAN WEWENANG BADAN PEMBERDAYAAN MASYARAKAT, PEREMPUAN DAN KELUARGA BERENCANA (BPMPKB) DALAM MENINGKATKAN KESEJAHTERAAN NELAYAN DI WILAYAH PESISIR KOTA TEGAL - Retno Saraswati, RIFKI ARDY SULARSO, Amiek Soemarmi, (Diponegoro Law Journal, 2012)
Community empowerment as crucial in the welfare of the public, especially fishermen in coastal areas Tegal that under present conditions are not able to escape the poverty trap, To that end, the authors elaborate further in legal writing entitled "Duties and Powers of the Agency for Community Empowerment, Women and family Planning (BPMPKB) in Improving Coastal Fishermen Welfare Tegal". The objective is to determine the duties and authority BPMPKB bamboozle the public and to determine the form of empowerment by BPMPKB in an effort to improve the welfare of fishermen in coastal areas Tegal. The research method used is the normative juridical done by examining library materials which are also called secondary data research law library. The results and conclusions note that BPMPKB Tegal has a fundamental duty carry out the preparation and implementation of regional policy in the field of community development, women's empowerment and child protection, family planning and food security. Tegal BPMPKB only provide guidance and disseminate the fishing community and in doing performance BPMPKB Tegal is more coordination to the Department of Marine and Agriculture Tegal has a special authority in the empowerment of coastal fishing communities Tegal. The suggestion is expected in the next period BPMPKB Tegal provides special programs for fishing communities through the empowerment of the fisheries sector.